Desire thinking as a confounder in the relationship between mindfulness and craving: Evidence from a cross-cultural validation of the Desire Thinking Questionnaire. (October 2017) - Chakroun-Baggioni, Nadia; Corman, Maya; Spada, Marcantonio M.; Caselli, Gabriele; Gierski, Fabien
Abstract: Desire thinking and mindfulness have been associated with craving. The aim of the present study was to validate the French version of the Desire Thinking Questionnaire (DTQ) and to investigate the relationship between mindfulness, desire thinking and craving among a sample of university students. Four hundred and ninety six university students completed the DTQ and measures of mindfulness, craving and alcohol use. Results from confirmatory factor analyses showed that the two-factor structure proposed in the original DTQ exhibited suitable goodness-of-fit statistics. The DTQ also demonstrated good internal reliability, temporal stability and predictive validity. A set of linear regressions revealed that desire thinking had a confounding effect in the relationship between mindfulness and craving. The confounding role of desire thinking in the relationship between mindfulness and craving suggests that interrupting desire thinking may be a viable clinical option aimed at reducing craving. Highlights: The structure of the Desire Thinking Questionnaire is confirmed in a French sample. Desire thinking is a confounder in the relationship between mindfulness and craving. Interrupting desire thinking may be linked to a reduction of craving.